Alcohol use in India: The road ahead - Prafulla Kumar Das
Prohibition has been incorporated in the Constitution of India among the Directive Principles of State Policy. But, the liquor manufacturers in India are able to glorify alcohol consumption by promoting drinking in congenial social settings and through glamour and celebrity status. This study surveyed articles on alcohol consumption to note down its impact on various fronts of social life. It was found that the tendency to consume alcohol had percolated down to the youth of India. The media played a leading role in encouraging alcohol use among the youth. In Kerala, the age of alcohol consumption was 19 in 1986, by 1990 it dropped to 17, and by 1994 the age came down to 14. The positive finding was that 60 per cent effect of prohibition could be achieved only by increasing the legal age of drinking from 18 years to 21 years. This paper aims to study the negative implications of alcohol use from different angles so that policy makers would probably take a stand on prohibition. The paper also aims to dissuade individuals to use alcohol. It (the paper) calls upon the supporters of alcohol use to reduce their vigor of persuasion. The study tries to identify the research gaps so that the cost and impact of alcohol on national economies could be studied comprehensively in future.